حديث «لاَ يُسْأَلُ الرَّجُلُ فِيمَا ضَرَبَ امْرَأَتَهُ»: دراسة تحليلية لإشكالاته وحلوله = Analytical study of the Ḥadith “A man should not be asked the reason he hits his wife" - Yaakob, Faridah; Mohammed Yaqub, Mohammed Abullais Shamsuddin; Muhammad, Fatimah (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2019)
تناول البحث بالدراسة والتحليل لحديث «لَا يُسْأَلُ الرَّجُلُ فِيمَا ضَرَبَ امْرَأَتَهُ»؛ فإن أغلب عوام الناس يفهمون معنى الحديث فهماً خاطئاً، وهو أن الحديث يمنع أن يسأل الزوج سبب ضربه زوجته مطلقاً، ويجيز ضرب الزوجة إما بحق أو بدون حق. واستخدمت هذه الدراسة المنهج الاستقرائي لجمع أقوال العلماء حول هذا الحكم، والمنهج التحليلي للوصول إلى المعنى الصحيح لهذا الحديث. وتوصلت الدراسة إلى عدة نتائج، من أهمها: أولاً: أن للعلماء في حكم سؤال الزوج عن ضرب زوجته حكمين، وهما مباح أو مكروه. ثانياً: أن إباحة ضرب الزوجة من منظور الخطاب القرآني والسنة تنحصر في حالة النشوز لا غيره، وله ثلاث مراحل تدريجية: بالقول أولاً، ثم بالفعل وهو الإعراض، ثم الضرب بشروط معينة. ثالثاً: اكتشف البحث حلولاً للإشكال في هذا الحديث، أولها: كشف الغموض في الحديث ومعالجته بنشر الفهم الصحيح لهذا الحديث في المجتمع، والثاني: تقترح الدراسة بعض الطرق لتكوين الأسرة المسلمة الناجحة حسب التعاليم الإسلامية. *********************************************************** This study investigates the Hadith “A man should not be asked the reason why he hits his wife”. Most people have wrong understanding towards this Hadith as it seems to prohibit people from clarifying the reason a husband hits his wife and grants him absolute permission in doing so regardless of whether or not he has a valid reason. The methodologies used in this study are inductive and analytical method in which several related materials from the Qur’an and Hadith are collected and analyzed in order to derive the authentic meaning of this hadith. Some of the findings discovered by this research are; First, there are two rulings regarding questioning the husband’s action of hitting his wife which are permissible (Mubah) or detestable (Makruh). Second, Qur’anic verses and hadith implies that wife-beating is only permissible in specific case which is disobedience (nusyuz), and must follow three stages begining with reminding the wife of her mistakes, followed by action indicating that the husband is displeased with her, which is separation and bed and then hitting -without incurring pain or injury- as the final resort. Third, this research discovers methods to solve this issue: the first one being curing the misunderstanding of this hadith and spreading its authentic meaning to the society; and the second is by proposing effective ways to build successful family institution according to the teachings of Islam.